Pengaruh Ukuran Perusahaan, Pertumbuhan Aset, Struktur Aset, Tingkat Utang Dan Modal Kerja Bersih Terhadap Profitabilitas - Mega Lestari; Eny Purwaningsih (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
This study aims to examine the effect of company size, asset growth, asset structure, debt level, and net working capital on the profitability of food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. This research employed a quantitative approach using secondary data obtained from the companies’ annual financial reports. The sampling technique used was purposive sampling, resulting in 23 companies with 69 observations. Prior to hypothesis testing, the data were evaluated for outliers, and observations identified as outliers were removed, resulting in 45 observations that met the classical assumption requirements. Data analysis was conducted using descriptive statistics, classical assumption tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination (Adjusted R²). The results indicate that company size and asset structure have a positive and significant effect on profitability. In contrast, debt level has a negative and significant effect on profitability, indicating that excessive leverage tends to reduce corporate profitability. Meanwhile, asset growth and net working capital do not have a significant effect on profitability. Simultaneously, all independent variables significantly influence profitability, with an Adjusted R² value of 0.429, indicating that 42.9% of the variation in profitability can be explained by the variables included in this study, while the remaining 57.1% is influenced by other factors outside the research model. These findings provide practical implications for managers in optimizing asset management and controlling debt to improve corporate profitability, as well as for investors in evaluating the financial performance of manufacturing companies.